HUBUNGAN INTENSITAS PENGGUNAAN INTERNET, INTENSITAS KOMUNIKASI PEER GROUP, STATUS SOSIAL EKONOMI DENGAN INTENSITAS MEMBACA BUKU PADA REMAJA KOTA SEMARANG - Afif Hazly Hasibuan; Tandiyo Pradekso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
The massive usage of internet often considered as the main factor from the shifting of conventional media usage, as the print book. In spite of that, peer group encouragement and economic ability are giving a contribution to people’s choices regarding to media usage. This research aims to determine the relation of internet usage intensity, peer group communication intensity, social economic status, with the intensity of reading book. This research is using reference group theory and literature review for determining every hypotesis in this research.For the sampling technique, this research is using the non-random sampling technique in convenient sampling method. The number of samples studied is 100 respondents with some characteristics, there are; domicile in Semarang, age range between 15 – 24 years old, active users of the internet and still reading a book. The result of first hypothesis testing is there is no correlation between internet usage intensity with the intensity of reading book with a value 0,071 of significance. The second hypothesis testing result is there is no correlation between peer group communication intensity with the intensity of reading book with a value 0,922 of significance. The third hypothesis testing result is there is a correlation between social economic status with the intensity of reading book with a value 0,019 of significance and -0,234 of correlation coefficient. Through this result, for increasing the intensity of reading book it is suggested that every content creator on the internet for making convergent content that directs every reader to read a book and for every person should bring his favorite books when interacting with their peer group. For book publishers, it is suggested for making brief and comprehensive content like the infographic, so every published book remains interesting to read.